2013
DOI: 10.2147/copd.s45081
|View full text |Cite
|
Sign up to set email alerts
|

The 6-minute pegboard and ring test is correlated with upper extremity activity of daily living in chronic obstructive pulmonary disease

Abstract: BackgroundUpper-extremity exercise is for pulmonary rehabilitation. The 6-minute pegboard and ring test (6PBRT) was developed to evaluate arm exercise capacity in patients with chronic obstructive pulmonary disease (COPD). The purpose of this study was to characterize the 6PBRT and evaluate its relationship with upper-extremity activities of daily living (ADLs) in COPD patients.MethodsTwenty outpatients with mild to very severe COPD underwent the 6PBRT and spirometry, and their maximal inspiratory and expirato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
1
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 15 publications
0
22
1
4
Order By: Relevance
“…However, we found no significant correlations between these variables. Our observations conflict with the findings of Takeda et al, 29 who found positive significant correlations between an unsupported arm functional test (6-minute pegboard and ring test) and measures of daily wrist activity (measured using an accelerometer) in individuals with COPD. However, the authors did not attempt to isolate arm activity from overall physical activity, and therefore the positive correlations of the 6-minute pegboard and ring test with the wrist accelerometer in their study may reflect a relationship between the overall level of physical activity with the individual's functional status.…”
Section: T a B L E 1 • Participant Characteristicscontrasting
confidence: 99%
“…However, we found no significant correlations between these variables. Our observations conflict with the findings of Takeda et al, 29 who found positive significant correlations between an unsupported arm functional test (6-minute pegboard and ring test) and measures of daily wrist activity (measured using an accelerometer) in individuals with COPD. However, the authors did not attempt to isolate arm activity from overall physical activity, and therefore the positive correlations of the 6-minute pegboard and ring test with the wrist accelerometer in their study may reflect a relationship between the overall level of physical activity with the individual's functional status.…”
Section: T a B L E 1 • Participant Characteristicscontrasting
confidence: 99%
“…33,34 The shuttle test, despite less use than the 6MWT, also has the ability to measure physical capacity changes in COPD submitted to an intervention. 35 In addition, unsupported upper-limb tests could also describe the functionality of COPD patients 36 and could be taken alone or in conjunction with the 6MWT or shuttle test.…”
Section: Discussionmentioning
confidence: 99%
“…recommendations on how to objectively measure the UL exercise capacity in individuals with chronic respiratory conditions remain scarce (18).…”
Section: Physical Assessmentmentioning
confidence: 99%